Effect of guineacorn/palm kernel-,meal based diet with niacin supplementation on the performance of broilers - OLOYO, R A. (The Indian Journal of Animal Sciences, 2013)
Commercial broiler chicks, 350 day-old, were randomly assigned to duplicate floor pens with 25 chicks each. They were fed a guineacorn-palm kernel-meal based diet supplemented with 0.0, 7.5; 15.0,22.5,30.0,37.5 and 45.0 mg niacin/kg feed for 42 days. Significantly poorer live-weight gain, feed intake and apparent utilization of nitrogen metabolizable energy. calcium and phosphorus, and a higher incidence of dermatitis and leg bone deformities in broilers on niacin-unsupplemented diets showed a deficiency of niacin in the basal diet which were all reversed with addition of 30.0 mg niacin/kg feed.